The Effects of Repeated Dyspnea Exposure on Response Inhibition - Sucec, Josef; Herzog, Michaela; Van den Bergh, Omer; Van Diest, Ilse; von Leupoldt, Andreas (Frontiers in Physiology, 2019)
In order to treat dyspnea (= breathlessness) successfully, response inhibition (RI) as a major form of self-regulation is a premise. This is supported by research showing that self-regulation is associated with beneficial behavioral changes supporting treatment success in patients. Recent research showed that dyspnea has an impairing effect on RI, but the effects of repeated dyspnea exposure on RI remain unknown. Therefore, the present study tested the effects of repeated resistive load-induced dyspnea on RI over a five-day period. Healthy volunteers (n=34) performed the standard version of the Stroop task during baseline and dyspnea conditions on the first and fifth testing day and underwent an additional dyspnea exposure phase on each testing day. Variables of interest to investigate RI were reaction time, accuracy as well as the event-related potentials late positive complex (LPC) and N400 in the electroencephalogram. Reduced accuracy for incongruent compared to congruent stimuli during the dyspnea condition on the first testing day were found (p<.001). This was paralleled by a reduced LPC and an increased N400 for incongruent stimuli during the induction of dyspnea (p<.05). After undergoing dyspnea exposure, habituation of dyspnea intensity was evident. Importantly, on the fifth testing day, no differences between baseline and dyspnea conditions were found for behavioral and electrophysiological measures of RI. These findings demonstrate that the impairing effect of dyspnea on RI disappeared after repeated dyspnea exposure in healthy participants. Translated to a clinical sample, it might cautiously be suggested that dyspnea exposure such as dyspnea perceived during physical exercise could reduce the impairing effect of dyspnea on RI which might have the potential to help increase self-regulation abilities and subsequent treatment efforts in dyspneic patients.